(NrUSSKIJ FOLXKLOR (B:s (Nu^EBNOE POSOBIE (B/s - (NaNIKIN(B, (NwLADIMIR pROKOPXEWI^s ((NmOSKWA (B:s (NwYS[AQ [KOLA (B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 273 - 280. (NpREDM(B. (NUKAZ(B.: (NS(B. 281 - 284s
Keywords: (NrUSSKIJ FOLXKLORs